Pengaruh Proses Distorsi dan Lupa Dalam Perkembangan Peserta Didik - Ahyani Mirah Liani (Journal of Mathematics, Statistics and Applications, 2025)
This article presents an in-depth analysis of the process of distortion and forgetting in student development. Combining literature from various scientific disciplines such as cognitive psychology, neuroscience, and education, this study discusses the mechanisms, impacts, and implications of the process of distortion and forgetting on students' learning and development. The method used is a descriptive method using a literature review approach. The aim of this research is to determine the relationship or connection between the processes of distortion and forgetting in learning or student development. The research results show that the influence of the distortion and forgetting process has a significant role in students' development in making decisions. Awareness of distortions and forgetting can help students identify and overcome potential risks in decision making. On the other hand, forgetting information, forgetting tendencies, and forgetting consequences can have a serious impact on students' evaluation and decision making planning.